Five children and it - Nesbit, E. (Edith), 1858-1924. (Mineola, N.Y. : Dover Publications, 2008)
When four brothers and sisters discover a Psammead, or sand-fairy, in the gravel pit near the country house where they are staying, they have no way of knowing all the adventures its wish-granting will bring them.
"Unabridged republication of the text of Five children and it, as published by T. Fisher Unwin, London, in 1902"--T.p. verso.
Keywords: Fairies -- Fiction; Wishes -- Fiction; Brothers and sisters -- Fiction; Great Britain -- History -- Edward VII, 1901-1910 -- Fiction